Study of kinematic parameters of android robot in automated synthesis of motions on velocity vector - F. N. Pritykin (Омский научный вестник)
The modernization of the method of synthesis of motions of manipulators by speed vector allows to exclude motions the emergence of dead ends in the process of computer simulation. The developed algorithm is based on the use of a database characterising the values of kinematic parameters that specify the permissible instantaneous states of the mechanism of the manipulator at different positions. The graphical representation of the hypersurface of the reflective relationship of the specified parameters from the values of the generalized coordinates is made. On the basis of this, a method for determining the above kinematic parameters is proposed, which makes it possible to reduce the time for calculating intermediate configurations on a given trajectory of the output link and to eliminate the occurrence of deadlock situations.